Detection of Sapoviruses in two biological lines of Tunisian hospital wastewater treatment. Issue 4 (4th July 2019) - Ibrahim, Chourouk; Hammami, Salah; Chérif, Nadia; Mejri, Selma; Pothier, Pierre; Hassen, Abdennaceur
ABSTRACT: The efficiency of rotating biodisks and natural oxidizing lagoon procedures is investigated at a Tunisian semi-industrial pilot plant, El Menzeh I, where the wastewater is mainly provided by three different neighbouring hospital clinics. Throughout 2011, 102 wastewater samples were collected from the two mentioned wastewater treatment procedures. Results showed that the Sapovirus (SaV) frequency was approximately 29.4% using the real-time reverse transcription polymerase chain reaction (RT-PCR) technique, and about 16.6% using the conventional RT-PCR. Also, the SaV genogroups and genotypes were identified and genotyping revealed that all of the four Tunisian SaV strains obtained belonged to the two genogroups GIV.1 and GGI.3. In addition, two new genotypes, D and C, were detected. A moderate decrease in the SaV frequencies was observed at the exit of the two treatment processes and the SaV removal rate was around 90% in the natural oxidizing lagoons and 94% in the rotating biodisks procedure showing the temperate sensitivity of these viruses to the implemented biological wastewater. Therefore, an urgent disinfection process should be implemented downstream of the two biological treatment procedures for safe release of treated effluent in the different natural environments. Abbreviations: NoV: Noroviruses; SaV: Sapoviruses; EC: Electrical Conductivity; COD: Chemical Oxygen Demand; BOD5: Biological Oxygen Demand; SS: Suspended Solids; NH4-N: Ammonium Nitrogen; P-PO4: Ortho-Phosphate; AlCl3: aluminum chloride